Pyracantha fortuneana (Maxim.) Li: A comprehensive review of its phytochemistry, pharmacological properties, and product development - Wang, Lingyu; Li, Ruolan; Zhang, Qing; Liu, Jia; Tao, Ting; Zhang, Ting; Wu, Chunjie; Ren, Qiang; Pu, Xufeng; Peng, Wei (Frontiers in Sustainable Food Systems, 2022)
Pyracantha fortuneana (Maxim.) Li has been used as a herbal medicine in China in its long history. Since ancient times, the fruits of P. fortuneana has been considered a functional food to improve various diseases. Many bioactive substances, including proanthocyanidins, phenols, polysaccharides, and dietary fibers, have been isolated and identified from the P. fortuneana, which possess diverse biological properties both in vitro and in vivo. Although the researches on the P. fortuneana have achieved extensive progress, the systematic study of its biological activities is still relatively lacking. In addition, accumulating researches focus on the landscape value of the P. fortuneana and the development of its by-products. The by-products of P. fortuneana, which show good development potentials in the field of agricultural production and environmental protection, are important for improving the economic value of P. fortuneana and its significance. After extensive reviewing and analyzing the existing published articles, books, and patents, this study aims to a systematic and summarized research trends of P. fortuneana and its phytochemical compositions, nutritional values, pharmacological effects and health benefits of its extracts/monomers, which would be beneficial for the future development of this medicinal plant as functional food or drugs.